A Comparative Analysis of Research Studies on Educational Administration Published in Some Arab Educational Refereed Journals and American in the light of the Sociology of Knowledge and the ’Structure of Scientific Revolutions’ - Jubran, Ali (Jordan Journal of Educational Sciences, 2006)
This study aimed at analyzing research studies on Educational Administration in 19 Arab refereed educational journals and the American Journal of “Educational Administration Quarterly”. The researchers approached the topic from the perspective of the “Sociology of Science”, and Kuhn’s “Structure of Scientific Revolutions”. The study revealed a humble number of studies (70) scattered in 19 Arabic journals compared with 492 studies published by the EAQ. In both settings, the majority of studies were conducted by academicians. In terms of methodology and instruments, Arab authors were more inclined towards the descriptive studies, while there was a diversity of methods employed by the authors of EAQ. The majority of Arab studies were survey-like. By contrast, the contributions to EAQ were more interested in articulating administrative models, perspectives, alternatives and critiques to administration. The study ended with conclusions and recommendations.(